A Preliminary Efficacy and Feasibility of an Obstructive Sleep Apnea Educational Intervention in Oman. - Al Mezeini, Khamis Abdallah (Preliminary Efficacy & Feasibility of an Obstructive Sleep Apnea Educational Intervention in Oman, 2017)
Background: Obstructive sleep apnea (OSA) is chronic disorder that contributes to multiple physiological and psychological conditions. Obstructive sleep apnea contributes to high rates of morbidity and mortality and has substantial impacts on both health care costs and the quality of life for affected individuals and their families. Healthcare providers -- particularly primary health care nurses -- are ideally situated to interrupt the cascading consequences of OSA if they are equipped with evidence-based knowledge about the disease process and appropriate methods for screening, education, and preventive interventions. Purpose: The purpose of the study was to test the preliminary efficacy and feasibility of an online health educational intervention on the knowledge and attitudes of OSA among primary health care nurses in Oman. Methods: This study was designed to assess the preliminary efficacy and feasibility of an online educational program on OSA by randomly assigning subjects to either a treatment (OSA content) or attention control (diabetes content) group. At baseline, the OSA knowledge and attitudes of both groups were assessed by the Obstructive Sleep Apnea Knowledge and Attitudes (OSAKA) questionnaire; both groups also completed the Diabetes Basic Knowledge Test (DBKT) to use for control comparisons. Following randomization, the intervention group viewed a 15-minute narrated video on "Brief Introduction to OSA for Omani Nurses" and the control group viewed a similarly formatted 15-minute narrated video on diabetes. The intent was for the subjects in both groups to complete a posttest that included both the OSAKA and DBKT instruments; however, due to a programming error, the software did not present the DBKT to the intervention subjects and did not present the OSAKA instrument to the control subjects as intended. Therefore, the results describe the findings from a one-group, pretest-posttest intervention study to assess the preliminary efficacy and feasibility of the educational intervention. Feasibility data were also collected with face-to face interviews with a convenience sample of nurse administrators who oversee primary health care nurses in health centers in the Al-Batinah governorate in Oman. Results: Overall, the baseline OSA knowledge scores for the entire sample (N=156) were very low (M=8.87, SD=2.91; median=9, range 0-15 out of possible 18 points). There were no significant relationships between OSA knowledge and any of the demographic variables. There was no significant difference in the mean OSA knowledge scores (p=0.80, t =0.26) between the intervention group (M=8.90, SD=2.68, n=73) and the control group (M=8.84, SD=3.12, n=83) at baseline. Primary health care nurses in the intervention group (n = 73) had a significant improvement in posttest knowledge scores on the OSAKA as compared to pretest scores ( p = .037, t= -2.1). After the online OSA educational intervention, 91.8% (n=67) of participants (n=73) indicated they were "likely" or "very likely" to recommend the online video to other health professionals. Although posttest attitudes were higher than baseline for the intervention group, the difference did not reach statistical significance. Implications for Practice: The low levels of OSA knowledge in this sample of primary health care nurses may indicate that their ability to identify patients at risk for OSA, assess at-risk patients appropriately, or refer as needed to physicians is limited. Nursing educators may consider integrating content about sleep disorders -- and OSA -- into the baccalaureate nursing curricula. Continuing education programs might offer focused programs on sleep disorders and OSA to raise awareness among practicing nurses. Conclusion: Primary health care nurses in Oman are expected to assess patients, identify health risks, and refer as necessary to physicians or other practitioners. In this sample of primary health care nurses, knowledge about OSA was limited; low knowledge of risk factors, symptoms, and treatment options may undermine the nurses' ability to assure that patients who may have OSA are referred appropriately. Implications for basic nursing curricula and continuing education are offered.